Relación entre el mobbing y el síndrome del Burnout en colaboradores: revisión aplicada - Sihuay Sihuay, Lucia Belen (2023)
Mobbing directly affects the performance, motivation and well-being of employees, generating economic and productivity losses. The objective of this work is to identify the relationship between mobbing and Burnout syndrome. For this, a systematic search, review and analysis of research articles from psychology journals was carried out and in accordance with the required criteria of the PRISMA guide. The information was obtained from the Web of Science and Scopus databases, of which ten were selected for the analysis of the works that investigated mobbing and Burnout syndrome. The methodology of the selected studies was descriptive-correlational, quantitative and cross-sectional. It was possible to observe that in the presence of mobbing there is a greater probability of developing Burnout syndrome. In conclusion, a statistically significant relationship is observed between mobbing and Burnout syndrome, which answers the research question posed. It is recommended that future research should be of a longitudinal design to obtain results for an evolutionary perspective and be investigated from a qualitative approach to diversify information, applicable to practice in the organizational field.